2017
DOI: 10.1080/10253890.2017.1303472
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ parenting stress is associated with salivary cortisol profiles in children with attention deficit hyperactivity disorder

Abstract: The aim of this study was to explore the relation between mothers' parenting stress and the functioning of the hypothalamic-pituitary-adrenal axis (HPAA), as expressed by daily salivary cortisol concentrations, in their children diagnosed with attention deficit hyperactivity disorder (ADHD). Seventy-five children aged 6-11 years diagnosed with ADHD predominant hyperactive-impulsive/combined (ADHD-HI/C, N = 49) and inattentive symptoms (ADHD-I, N = 26) and 45 healthy peers and their mothers participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…At the extreme of disrupted parenting, Child Protection agency referred individuals with histories of maltreatment exhibit reduced morning cortisol (Bernard, Frost, Bennett, & Lindhiem, ). However, others have found higher morning cortisol has been associated with lower parenting quality (Clowtis, Kang, Padhye, Rozmus, & Barratt, ) and greater maternal report of dysfunctional interactions (Korpa et al, ). Likewise, the current analysis revealed the mediation pathway through maternal parenting was associated with heightened morning cortisol.…”
Section: Discussionmentioning
confidence: 98%
“…At the extreme of disrupted parenting, Child Protection agency referred individuals with histories of maltreatment exhibit reduced morning cortisol (Bernard, Frost, Bennett, & Lindhiem, ). However, others have found higher morning cortisol has been associated with lower parenting quality (Clowtis, Kang, Padhye, Rozmus, & Barratt, ) and greater maternal report of dysfunctional interactions (Korpa et al, ). Likewise, the current analysis revealed the mediation pathway through maternal parenting was associated with heightened morning cortisol.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of stress, in the current study of women with young children, we focused on inclusion of specific stressors that have been shown to be quite prevalent and influential for this segment of the population and are known risk factors for decrements in health and cognitive function. These include living in a poorly regulated and noisy or "chaotic" home environment [30], caring for a child with disruptive behavior problems such as aggression or inattention symptoms [13], being a single parent [31], from a lower socioeconomic bracket [32], facing adverse life events such as negative job or relationship changes [33], facing chronic daily parenting hassles [34], lacking access to social support from other adults [35], and experiencing "role overload" at home and work [36].…”
Section: Stress Sleep and Cognitionmentioning
confidence: 99%
“…There is considerable heterogeneity in cognitive functioning across the lifespan, with certain types of cognitive abilities beginning to decline in the 20s and some not beginning noticeable decline until later ages [10]. In the current study, we addressed these questions by focusing on mothers in their 20s through 40s-since for many women, these years are marked by the entry into parenthood [i.e., in the United States, nearly 90% have a child by the time they are 44; 11], which results in both disrupted sleep and higher stress due in part to childrearing demands [12,13]. While extensive literature has covered changes in mothers' postpartum sleep, fewer studies have examined sleep in mothers of toddlers, after the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, poor response inhibition has been associated with nonspecific physiological arousal making the behavioural inhibition system particularly relevant for the association between stress system dysfunction and ADHD (King, Barkley, & Barrett, 1998). Studies have reported attenuated HPA axis reactivity among children with ADHD and no comorbid conditions (Angeli et al, 2018; Isaksson, Nilsson, Nyberg, Hogmark, & Lindblad, 2012; Korpa et al, 2017; Ma, Chen, Chen, Liu, & Wang, 2010), associated with several of the core symptoms of ADHD (Pesonen et al, 2011). Moreover, there is inconclusive evidence for the associations between ADHD and autonomic dysregulation in children (Imeraj et al, 2012; Robe, Dobrean, Cristea, Păsărelu, & Predescu, 2019).…”
Section: Introductionmentioning
confidence: 99%